PEMBERIAN MAHAR DALAM BENTUK HIASAN UANG KERTAS MENURUT PERSPEKTIF HUKUM ISLAM - Maki, Leo Perkasa (Institut Agama Islam Negeri Metro, 2021)
This article aims to examine and analyze the giving of dowries in the form of decorative banknotes from the perspective of Islamic law. This study was carried out because the marriage procession for the Indonesian people does not only refer to religious provisions, but the culture that develops in the community itself, sometimes even cultural nuances are thicker than religious provisions, including the current developing culture is the giving of dowries in the form of banknotes. Original by being formed into various variants of images, such as mosques, fans, doves, and so on. The giving of dowries in the form of original banknote decorations according to Islamic law is not prohibited, and from an aesthetic point of view, dowries that are formed into wall hangings do have benefits because they look so beautiful, but it's good that the basic materials used for wall decoration are not real money but toy banknotes that are only symbolic at the time of the marriage contract without losing its aesthetic value.